Hemichorea - hemiballismus in undiagnosed diabetes mellitus asian female patient associated with non ketotic hyperglycemia: putamenal and caudate nucleus lesions on magnetic resonance imaging - Doshi, Rajkumar Prakashbhai; Patel, Viralkumar; Patel, Keyur; Patel, Maulik (International Journal of Research in Medical Sciences, 2016)
Hemichorea-Hemiballismus (HCHB) with corresponding putaminal T1 hyperintensity on MRI has occasionally been reported in diabetes mellitus (DM) type 2 with non ketotic hyperglycemia, which is believed to be pathogenetically related to HCHB. A 65 year female presented with fever, diarrhea, and involuntary movements on all 4 limbs in known case of diabetes mellitus type 2, hypertension, chronic heart failure and chronic renal failure. We report occurrence of HCHB in a female patient with DM type 2, Hypertension and acute renal failure.